Effect of inner ear malformations on intraoperative ECAP thresholds and postoperative auditory performance - Kim, Jeong‐Seo; Hong, Sung Hwa; Moon, Il Joon (Laryngoscope investigative otolaryngology, 2022)
Objectives This study sought to characterize the influence of inner ear malformations (IEMs) on intraoperative electrically evoked compound action potential (ECAP) and auditory performance to better understand the underlying pathophysiology related to variabilities in cochlear implant (CI) outcomes that individuals with malformed cochlea may present. Methods The medical records of 222 ears implanted with Cochlear Nucleus CI were reviewed. Of the total, 64 ears had radiologic evidence of IEMs, and 158 ears were normal. Individuals with IEMs were grouped based on the severity of anomalies; 38 had mild IEMs (e.g., enlarged vestibular aqueduct, incomplete partition type II, etc.) and 26 had severe IEMs (e.g., cochlear nerve hypoplasia, common cavity, etc.). Intraoperative ECAP thresholds obtained via neural response telemetry (NRT) and the categories of auditory performance (CAP) scores measured at 12 months postoperative were compared and correlated. Results Absent ECAP responses were more apparent in the IEM group. ECAP thresholds were significantly elevated in the severe IEM group, while the mild IEM group had ECAP thresholds comparable to the normal group. The mild IEM group achieved CAP scores similar to the normal control. Patients in the severe IEM group showed significantly lower CAP scores at 12 months postoperative. Significant negative relationships existed between ECAP thresholds and CAP scores obtained from all subjects. Conclusion Measurable ECAP responses and NRT thresholds varied across groups. The inverse relationship between NRT thresholds and CAP scores may suggest that electrophysiological responses measured during surgery may potentially be indicative of postoperative performance in our CI population. Level of Evidence 2b. Measurable ECAP responses and NRT thresholds varied across groups. The inverse relationship between NRT thresholds and CAP scores may suggest that electrophysiological responses measured during surgery may potentially be indicative of postoperative performance in our CI population.